Contrasting bacterial and archaeal distributions reflecting different geochemical processes in a sediment core from the Pearl River Estuary - Wang, Wenxiu (AMB Express, 2020)
Microbial community structure and metabolic activities have profound impacts on biogeochemical processes in marine sediments. Functional bacteria such as nitrate- and sulfate-reducing bacteria respond to redox gradients by coupling specific reactions amenable to relevant energy metabolisms. However, similar functional patterns have not been observed for sedimentary archaea (except for anaerobic methanotrophs and methanogens). We coupled taxonomic composition with comprehensive geochemical species to investigate the participation of distinct bacteria and archaea in sedimentary geochemical cycles in a sediment core (300 cm) from Pearl River Estuary (PRE). Geochemical properties (NO(3)(−), dissolved Mn and Fe, SO(4)(2+), NH(4)(+); dissolved inorganic carbon (DIC), δ(13)C(DIC), dissolved organic carbon (DOC), total organic carbon (TOC), δ(13)C(TOC), and fluorescent dissolved organic matter (FDOM)) exhibited strong depth variability of different trends. Bacterial 16S rRNA- and dsrB gene abundance decreased sharply with depth while archaeal and bathyarchaeotal 16S rRNA gene copies were relatively constant. This resulted in an increase in relative abundance of archaea from surface (11.6%) to bottom (42.8%). Network analysis showed that bacterial groups of Desulfobacterales, Syntrophobacterales and Gammaproteobacteria were significantly (P < 0.0001) associated with SO(4)(2−) and dissolved Mn while archaeal groups of Bathyarchaeota, Group C3 and Marine Benthic Group D (MBGD) showed close positive correlations (P < 0.0001) with NH(4)(+), δ(13)C(TOC) values and humic-like FDOM. Our study suggested that these bacterial groups dominated in redox processes relevant to sulfate or metal oxides, while the archaeal groups are more like to degrade recalcitrant organic compounds in anaerobic sediments.